Perception of mothers towards male nursing students during clinical practice in obstetric ward In Hospital Universiti Sains Malaysia - Yusuf, Siti Nur Hasanah Ahmad (Universiti Sains Malaysia, 2023)
In many countries, women continue to dominate the nursing field. Social challenges for male nursing students result in discrimination from patients and caregiver. This restricts their ability to get the skills they need and affects their clinical practise experience, leading to a theory-practice gap. In addition, male nursing students have less opportunity to perform procedures while on the obstetric ward than their female colleagues as a result of this bias. A cross-sectional study was carried out to study the perception of mothers towards male nursing students during clinical practice in Obstetric ward, Hospital Universiti Sains Malaysia. A total of 124 mothers in Hospital USM who fulfilled the inclusion and exclusion criteria were selected randomly. Data collected were statistically analysed using the SPSS software version 26.0. Pearson’s Chi-Square were used for data analysis. This study shows that 75 (60.5%) of mothers have a positive level and 49 (39.5%) of mothers have a negative level perception towards male nursing students. The result of this present study revealed that there is no significant association of selected socio demographic factors (age, educational level and gender preference) with the level of mothers’ perception towards male nursing students (p=0.197), (p=0.060) and (p=0.649) respectively.